Selenium and its mechanisms mitigate cadmium toxicity in plants: Promising role and future potentials - Javed Hussian Sahito; Chenhui Ma; Jihong Zhang; Jianxin Li; Jiawen Zhao; Liqin Mu; Yuanyuan Zhang; Zeeshan Ghulam Nabi Gishkori; Dong Ding; Xuehai Zhang; Jihua Tang (Ecotoxicology and Environmental Safety)
Cadmium (Cd) is a highly toxic metal that poses a threat to human health and animals through food chain as well as impacts on plants even at low concentrations. It is a global environmental issue due to its widely distributed and has natural source and increasing anthropogenic activities such as metal industries, sewage sludges, mining, wastewater, chemical incidents, combustion emissions, and phosphate fertilizers increase the Cd concentration in the environment. In this review, we have discussed the source of Cd in the environment, the impacts of soil physiochemical properties on Cd, dynamics of Cd uptake mechanism, translocation, distribution, and toxic effects of Cd in plants. In crops, Cd toxicity reduces the uptake and translocation of essential nutrients and water and disrupts crucial physiological, biochemical, and molecular processes including photosynthesis, ROS homeostasis, activity of enzymes, cell death, leading to inhibits plant growth, resulting in yield losses. Additionally, potential remediation strategies and defense mechanisms are also highlighted. Although, plants have a complex defense mechanism against Cd toxicity but these mechanisms are often insufficient to address high concentrations of Cd. In addition, selenium (Se) is an important trace element for human, animals, and plants, and has shown remarkable potential to mitigate Cd toxicity in plants. Supplementation with Se minimize the detrimental effects of Cd by enhancing physiological, biochemical, and molecular functions, while also promoting Cd immobilization, co-precipitations, and compartmentalization. However, supplementation and mechanisms of Se and its other forms on plant performance in Cd-contaminated soils remain largely unclear. Thus, focuses on the promising role of Se supplementation and its underlying mechanism under Cd stress in plants, how Se can protect against Cd toxicity to plants by using different application methods, and increasing sequestration of Cd in cell walls by reducing the bio-availability of Cd in soil. Additionally, we also discussed research gaps and future research of Se to alleviate Cd induced toxicity. Taken together, low supplementations of Se and Se-NPs mitigate the human health risk associated with Cd toxicity in plants, especially in lightly contaminated soil. Overall, findings of this review will help to improve our understanding role of Se and its different forms such as Se-NPs to mitigate Cd toxicity and will offer deep knowledge for developing promising strategies to address the environmental challenges threatened by Cd toxicity in crops and improve agricultural productivity in Cd contaminated soils.